Auditory temporal processing in patients with temporal lobe epilepsy - Lavasani, Azam Navaei; Mohammadkhani, Ghassem; Motamedi, Mahmoud; Karimi, Leyla Jalilvand; Jalaei, Shohreh; Shojaei, Fereshteh Sadat; Danesh, Ali; Azimi, Hadi (Epilepsy & behavior, 2016)
Auditory temporal processing is the main feature of speech processing ability. Patients with temporal lobe epilepsy, despite their normal hearing sensitivity, may present speech recognition disorders. The present study was carried out to evaluate the auditory temporal processing in patients with unilateral TLE. The present study was carried out on 25 patients with epilepsy: 11 patients with right temporal lobe epilepsy and 14 with left temporal lobe epilepsy with a mean age of 31.1years and 18 control participants with a mean age of 29.4years. The two experimental and control groups were evaluated via gap-in-noise and duration pattern sequence tests. One-way ANOVA was run to analyze the data. The mean of the threshold of the GIN test in the control group was observed to be better than that in participants with LTLE and RTLE. Also, it was observed that the percentage of correct responses on the DPS test in the control group and in participants with RTLE was better than that in participants with LTLE. Patients with TLE have difficulties in temporal processing. Difficulties are more significant in patients with LTLE, likely because the left temporal lobe is specialized for the processing of temporal information. •This study aimed to evaluate auditory temporal processing in patients with unilateral temporal lobe epilepsy utilizing GIN and DPS tests.•The mean of GIN threshold in the right ear and left ear in control subjects obtained better than participants with LTLE and RTLE.•The percentage of correct response of DPS test in control subjects and participants with RTLE was better than participants with LTLE.•Patients with temporal lobe epilepsy have a disorder in auditory temporal processing. This disorder in patients with LTLE are more significant.